PENGARUH KOMPENSASI, BEBAN KERJA, DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN - Jienendra Ichsan Pradana; Heni Susilowati (LPPM Politeknik Pratama, 2022)
The idea of this research is to reveal the relationship of employee interest in terminate the employment relationshif at PT. Cartini Lingerie Indonesia Unit 2 of the factor of compensation, workload and job satisfaction. Sources of data in the form of information collected through simple random sampling of questionnaires given to 263 employees. While SPSS 25.0 is used as the main tool to process data, the results show that compensation has an insignificant negative effect on turnover intention, then workload and job satisfaction substantially effect turnover intention. The results of the F test found that compensation, workload and job satisfaction simultaneously had an effect. The contribution of the three test variables is 83% to the dependent variable while the remaining 17% comes from factors outside the research factor.